Itaconic Acid Production by Novel Aspergillus Niveus in Solid State Fermentation Using Agrowastes - Gnanasekaran, R; Saranya, P; Yuvashree, S; Yuvaraj, D; Saravanan, A; H. Smila, K; Anli Dino, A (International Journal of Engineering and Technology, 2018)
Itaconic acid (IA) is an organic compound. This dicarboxylicacid is a white solid that is soluble in water, ethanol, and acetone. Historically, itaconic acid was obtained by the distillation of citricacid, but currently it is produced by fermentation. Itaconic acid is essentially utilized as a co-monomer in the generation of polymers, for example, tar, plastic, elastic, paints, surfactant with applications in the paper and structural covering industry.. The fermentative production of Itaconic acid was probably achieved by the filamentous fungus Aspergillus terrus, Aspergillus itaconicus and mainly by Aspergillus niger. In the present work, an attempt was made to produce IA by Aspergillus niveus employing Solid State Fermentation (SSF) from various agro wastes like rice bran, rice husk,tamarind seed,wheat stuff and sugarcane bagasse as carbon substrates, which was pretreated in order to soften it.10 g of each substrate was taken in a 500 ml conical flasks separately and supplemented with 40 mL nutrient solution containing glucose, at pH 3.5. One milliliter inoculum containing 1×107 spores was added and moisture was maintained at 70%. After incubation at 32°C for 14 days, the acid production was estimated by spectrophotometric method and by HPLC analysis. Interestingly, the yield of itaconic acid was promising with all the above substrates, where tamarind seed, sugarcane bagasse and rice bran supported higher yields.